Obtenção e caracterização de óleo, proteína e etanol 2G de híbridos de canola semeados em diferentes épocas - Oliveira, Marília Boff de (2022)
Rich in oil and protein, a canola, Brassica napus is one of the main oilseed crops grown in the world, being used both in human and animal food and in the production of biofuels. In addition to the application, canola is a very broad crop adapted in cold regions, being promissory mainly in the southern region of Brazil. Aiming to find ways to adjust the definition of harvest and harvest times, in addition to renewable energy production systems, this work evaluated different sowing varieties of two canola hybrids selected for direct harvest and harvest by cut row, both times. with and without adjuvant sealant application. In addition, plan to evaluate these factors in oil production, influence, and fermentable sugars for 2G generation ethanol production. This thesis was three seasons, field in three seasons, in three stages: in the first season, the work was carried out with the cultivation of two canola hybrids Hyola 575 CL and Hyola 575 CL and Hyola 3, cultivated in 2019, 2021 and 2021, sown in three different ones. They were productive performance, oil content, protein, and collection method. The observed stage was the first time that presented the highest grain yield and canola is an extremely sensitive crop to climatic conditions, having its yield and quality of meteorological grains in these climatic conditions. The cut-row harvesting method with adjuvant application was the method that resulted in the lowest harvest losses. In the second stage of sugar, the potential for production of fermentable from the subcritical hydrolysis of canola biomass was studied. The most successive levels of sugar were found in the siliques of Hyola 433 with 10.2 g.100-1 g of biomass and stalks of Hyola sugar 575 CL with 11.5 g.100-1 g of biomass, showing high levels of xylose and cellobiose. In the third step, the levels of fatty acids present in the canola oil and the fermentative potential of the hydrolysates in the production of 2G ethanol were determined. High levels of oleic, linoleic, and palmitic compounds were observed in the oil. The use of canola biomass is promising in the production of 2G ethanol, reaching ethanol production up to 31.48% for the Hyola 575 CL hybrid in the 2019 harvest. Thus, canola, in addition to containing high levels of protein and oil, with good chemical quality, is one of the main raw materials for biodiesel production. These residual biomasses present great potential for the production of ethanol, expanding the possibilities of use and adhesion of the culture.